Effects of live Brucella abortus strain 19 vaccine on reindeer - Dieterich, Robert A.; Morton, Jamie K. (Rangifer, 1989)
Twenty female and seven male reindeer (Rangifer tarandus) were vaccinated subcutaneously in the right shoulder with a 1-ml dose of approximately 1.2 x 108 colony forming units of Brucella abortus strain 19, the standard reduced dose for cattle. An additional three females and one male served as non-vaccinated sentinels. Brucella abortus strain 19 was isolated from two of three fetuses aborted by vaccinated females during the first of two fawning seasons. Serologic titers to brucellosis in the vaccinates peaked by 46 days post-vaccination. Shedding of B. abortus strain 19 by vaccinated animals was indicated by seroconversion of all four sentinels. Titers in the sentinels were low and sporadic. Brucella abortus strain 19 was isolated from the tissues and fetus of a pregnant female 51 days post-vaccination and from the carpal joint of another female 7 months post-vaccination. Based on these results and a previous challenge experiment, it was concluded that Brucella abortus strain 19 is not a suitable vaccine to use in a brucellosis control program in reindeer.